2001
DOI: 10.1007/s004310100728
|View full text |Cite
|
Sign up to set email alerts
|

Latent coeliac disease in a child with epilepsy, cerebral calcifications, drug-induced systemic lupus erythematosus and intestinal folic acid malabsorption associated with impairment of folic acid transport across the blood-brain barrier

Abstract: Impairment of intestinal folic acid absorption with a defect in folic acid transport across the blood-brain barrier has been demonstrated in a case of epilepsy and cerebral calcifications associated with coeliac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…Several case reports of patients with both CD and SLE were published in the 1980s and 1990s 11,12,13,14,15,16 . In a report by Rensch, et al , 24 of 103 patients (23.3%) with SLE tested positive for antigliadin antibodies but none were positive for endomysial antibodies nor had small intestinal changes consistent with CD 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several case reports of patients with both CD and SLE were published in the 1980s and 1990s 11,12,13,14,15,16 . In a report by Rensch, et al , 24 of 103 patients (23.3%) with SLE tested positive for antigliadin antibodies but none were positive for endomysial antibodies nor had small intestinal changes consistent with CD 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports and case series have suggested a possible association between CD and SLE 11,12,13,14,15, 16,17,18,19 , but earlier research has suffered from low statistical power. At least 2 studies have also reported a high prevalence of antigliadin antibodies in SLE but with substantially lower rates of histologically verified CD 17,19 , and because of their lack of a control group with non-SLE individuals, these studies were unable to estimate relative risks of SLE in CD.…”
mentioning
confidence: 99%
“…Some authors have speculated that mechanisms of metabolic deficiency may represent the principal cause of this association (2,23,30,31) . as being associated with celiac disease (50,52) .…”
Section: Introductionmentioning
confidence: 99%
“…Folate deficiency (serum and CSF) has been noted in many patients with CEC, 15 though is not universal. Folate deficiency has been suspected to be the cause of CEC in previous cases because of their co‐occurrence, and the link between folate deficiency and cerebral calcification in other situations (e.g.…”
Section: Discussionmentioning
confidence: 99%